Senam Hamil dalam Upaya Persiapan Fisik dalam Persalinan - Rochany Septiyaningsih; Frisca Dewi Yunadi; Dhiah Dwi Kusumawati (Poltekita: Jurnal Pengabdian Masyarakat, 2020)
One of the health problems in Indonesia is the Maternal Mortality Rate (MMR). The World Health Organization (WHO) states that maternal deaths are deaths that occur during pregnancy, childbirth, or within 42 days postpartum which can be caused either directly or indirectly to pregnancy. Pregnancy is a happiness that can be felt by pregnant women who plan and look forward to it. During pregnancy, changes will occur both physical and psychological changes. Psychological changes also occur in pregnant women especially just before delivery. Pregnant women feel anxious because of hormonal changes and thoughts before delivery. Exercise and relaxation techniques during pregnancy are needed to reduce the anxiety of pregnant women. Pregnant gymnastics is one of the sports activities that mothers can do during pregnancy. The aim of community service is to increase the knowledge of pregnant women about pregnancy exercise and teach pregnancy exercise. The target community service is 10 pregnant women in Tambakreja Village. This service begins with health education about pregnancy exercise and then continues with pregnancy exercise practice. As a result of community service, there was an increase in knowledge by 38% from before counseling to counseling. Pregnant women are also able to practice pregnancy exercises properly.